2010
DOI: 10.1371/journal.pbio.1000480
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Cis- and Trans-Regulation of Human Gene Expression

Abstract: Using genetic and molecular analyses, we identified over 1,000 polymorphic regulators that regulate expression levels of human genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
158
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 72 publications
(98 reference statements)
4
158
0
Order By: Relevance
“…We observed good agreement between expression values for biological replicates used between the studies (average Pearson correlation (r) between expression values ¼ 0.87). Despite the much smaller size of the Cheung et al 33 data set, the association between rDNA dosage and GE were significantly correlated between studies (correlations between the strength of the association uncovered with expressed data from the Cheung et al 33 study and from the Montgomery et al 24 study: 18S:…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We observed good agreement between expression values for biological replicates used between the studies (average Pearson correlation (r) between expression values ¼ 0.87). Despite the much smaller size of the Cheung et al 33 data set, the association between rDNA dosage and GE were significantly correlated between studies (correlations between the strength of the association uncovered with expressed data from the Cheung et al 33 study and from the Montgomery et al 24 study: 18S:…”
Section: Resultsmentioning
confidence: 96%
“…These observations indicate that the major functional associations can be replicated independently within each population. Second, we performed association analysis on a subset of 27 overlapping CEU individuals for which RNA-seq data were generated from another study and processed through the same analysis pipeline 33,34 . We observed good agreement between expression values for biological replicates used between the studies (average Pearson correlation (r) between expression values ¼ 0.87).…”
Section: Resultsmentioning
confidence: 99%
“…We use three publicly available data sets, the Bottomly data (Bottomly et al (2011)), the Cheung data (Cheung et al (2010)), and the Pickrell/Montgomery ("MontPick") data (Pickrell et al (2010), Montgomery et al (2010)), as obtained from the recount site (http://bowtie-bio.sourceforge.net/recount/). The Bottomly data consist of RNA-Seq results from 21 samples of gene expression in the striatum in two strains of mice, 10 from the C7BL/6J strain and 11 from the DBA/2J strain.…”
Section: Resampling From Existing Data Setsmentioning
confidence: 99%
“…It is currently unclear to what extent eQTL common between cell types and tissues operate in cis-compared with trans-, as low power to detect trans-eQTL makes comparisons difficult (Gilad et al 2008;Ding et al 2010). Recently, several studies mapping cis and trans eQTL have suggested that considerable proportions of regulatory variation act in trans (Price et al 2008(Price et al , 2011Cheung et al 2010;Montgomery et al 2010;Pickrell et al 2010). This should lead us to reexamine the inferences drawn from comparing cis-eQTL overlap in multiple tissues.…”
mentioning
confidence: 99%